Assessment of chemical resistance of wild and cultivated Vigna species to the brown pod-bug Clavigralla tomentosicollis Stal (Hem., Coreidae) - Koona, P.; Osisanya, E.; Lajide, L.; Jackai, L.; Tamo, Manuele (Wiley, 2003)
The effects of secondary metabolites in different Vigna species on the development of Clavigralla tomentosicollis were investigated in an artificial seed system using different fractions of crude pod extracts, while the orientation response of this pod-bug to volatile extracts was studied using a dual-choice olfactometer. Feeding on the neutral fraction extracts, in contrast to the basic and acidic fractions, resulted in significantly higher mortalities, longer total developmental time, and lower growth index of the insects in comparison with controls. All volatile extracts elicited an avoidance reaction by C. tomentosicollis, except the volatile from the susceptible genotype IT84S-2246 which generally attracted as many insects as controls. Extracts from wild Vigna species showed higher activity than those from their cultivated relatives. The present study which has established that most secondary metabolites in cowpea pods were localized in the neutral fraction of the crude extract, could facilitate experiments on the separation and characterization of the toxic factors involved